1994
DOI: 10.2466/pms.1994.78.1.299
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Orientation in Perception of Reversible Figures

Abstract: We hypothesized that during perception of reversible figures the direction of gaze toward a specific perceptual focal point plays a determining role in the identification of the images, i.e., when subjects are asked by the experimenter to perceive one of the two images, a displacement of the eyes toward a specific spatial area of the figure occurs. For each image we think there is a particular point of the figure which acts as perceptual organizer. The stimuli were the Hill and Boring, Ehrenstein, Rubin, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Several studies support this hypothesis by showing that eye-fixation position biases the interpretation of ambiguous figures (Einhäuser et al 2004; Ellis and Stark 1978; Hochberg and Peterson 1987; Kawabata 1986; Kawabata et al 1978; Ruggieri and Fernandez 1994; Toppino 2003). Our results indicate that changing eye-fixation position by a saccade can transiently bias the interpretation of ambiguous figures.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies support this hypothesis by showing that eye-fixation position biases the interpretation of ambiguous figures (Einhäuser et al 2004; Ellis and Stark 1978; Hochberg and Peterson 1987; Kawabata 1986; Kawabata et al 1978; Ruggieri and Fernandez 1994; Toppino 2003). Our results indicate that changing eye-fixation position by a saccade can transiently bias the interpretation of ambiguous figures.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies, however, have shown that there is no such unique moment in the dynamics of EEG activity, and that switching is a process that extends over several hundreds of milliseconds (Nakatani and van Leeuwen 2005, 2006). As for eye-movements, it is well known that eye-fixation location biases the interpretation of ambiguous figures (Einhäuser et al 2004; Ellis and Stark 1978; Hochberg and Peterson 1987; Kawabata 1986; Kawabata et al 1978; Ruggieri and Fernandez 1994; Toppino 2003). This effect may be due to a sustained effect of top-down attention (Peterson and Gibson 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Fixation at different focal areas has been demonstrated to promote different perceptual interpretations with a variety of reversible figures (e.g., Gale & Findlay, 1983;García-Pérez, 1992;Georgiades & Harris, 1997;Kawabata, 1986;Ruggieri & Fernandez, 1994). However, a necessary role for eye movements has been questioned.…”
mentioning
confidence: 99%
“…Reversible or ambiguous figures like the Rubin's face/vase picture or the Necker cube have been used to study how people spontaneously alternate between two mutually exclusive interpretations of objectively stable pictures. The ability to reverse ambiguous figures depends on a combination of top-down and bottom-up processes (Intaitė, Noreika, Šoliūnas, & Falter, 2013;Long & Toppino, 2004), including recurring neural fatigue (review in Long & Toppino, 1981, gaze orientation (Ruggieri & Fernandez, 1994), mental imagery (Doherty & Wimmer, 2005) and context effects (Intaitė et al, 2013). A critical factor that determines whether participants are able to reverse an ambiguous figure is the amount of information given about the two potential interpretations (Mitroff, Sobel, & Gopnik, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For exploratory purposes, we also recorded children's eye movements to test whether picture morphing effects relate to individual differences in visual inspection of the pictures. In adult participants, impoverished control of selective attention led to lower sampling of informative parts of the stimulus (Tsal & Kolbet, 1985) and could explain variance in the picture morphing task (Ruggieri & Fernandez, 1994). Also, fixations recorded prior to object recognition predicted which interpretation of an ambiguous image was reported (Kietzmann, Geuter, & König, 2011).…”
Section: Introductionmentioning
confidence: 99%